2007
DOI: 10.1017/s0007114507742666
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and antioxidant capacity of plant extracts rich in polyphenols, given as a single acute dose, in sheep made highly susceptible to lipoperoxidation

Abstract: Plant extracts rich in polyphenols (PERP) could represent interesting alternative antioxidants but their use in ruminants needs further investigation since the antioxidant capacity of PERP could be altered by digestive processes. The aim of the study was to investigate the bioavailability and the antioxidant capacity of four PERP (rosemary; grape; citrus; marigold) in ruminants made highly susceptible to lipoperoxidation by a continuous linseed oil infusion (4 % DM) in the duodenum. The PERP were given, as a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
120
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 48 publications
10
120
1
2
Order By: Relevance
“…Again, it must be stressed that naringenin (aglycone fraction of naringin) was found to accumulate in the liver of the NARINGIN group (22.5 g/kg), whereas it was not detectable in the liver of CONTROL lambs. In fact, the glycosidic flavanone naringin is hydrolysed by ruminal microorganisms in order to allow absorption of the aglycone fraction (naringenin) by the animal (Gladine et al, 2007). After absorption, naringenin is transported to the liver, where it forms glucuronide and/or sulphate or methyl conjugates before being normally excreted through the urinary and faecal systems (Spencer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, it must be stressed that naringenin (aglycone fraction of naringin) was found to accumulate in the liver of the NARINGIN group (22.5 g/kg), whereas it was not detectable in the liver of CONTROL lambs. In fact, the glycosidic flavanone naringin is hydrolysed by ruminal microorganisms in order to allow absorption of the aglycone fraction (naringenin) by the animal (Gladine et al, 2007). After absorption, naringenin is transported to the liver, where it forms glucuronide and/or sulphate or methyl conjugates before being normally excreted through the urinary and faecal systems (Spencer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been suggested that different antioxidants given alone or combined with vitamin E could be more efficient at enhancing the antioxidant status of animals than the use of large doses of vitamin E (Gladine et al, 2007;Gobert et al, 2009 and.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the lack of statistical difference between treatments could be due, first, to the large individual variability in cortisol concentration between animals, and second, to the low rates of naringin used in this experiment. In fact, Gladine et al (2007) observed an increase in plasma antioxidant status when sheep were supplemented with supranutritional doses (10%) of naringin. The stress experienced by the animal when transported to the slaughterhouse exacerbates the lipoperoxidation of polyunsaturated fatty acids (Kannan et al, 2000).…”
Section: Antioxidant Parametersmentioning
confidence: 96%
“…For example, Gladine et al (2007), administered a single acute dose of plant extracts (rosemary, grape, citrus or marigold) directly into the rumen of sheep. The authors found that, after administration, epicatechin was detected in the plasma of animals dosed with grape extract, whereas naringenin was detected in the plasma of lambs dosed with citrus extract.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few studies, in which animals were fed with high doses of phenolic compounds, showed that simple phenolics are partially bioavailable in ruminants. Gladine et al (2007) detected monomeric phenolic compounds in the plasma of sheep receiving a ruminal infusion of galloylated condensed tannins or simple phenolics from grape or rosemary extracts. Moñino et al (2008) reported that the muscle from lambs raised on milk from ewes fed with a rosemary-enriched concentrate contained several of the phenols from rosemary (i.e.…”
Section: Introductionmentioning
confidence: 99%